St. Kitts and Nevis : Second Review Under the Stand-By Arrangement and the Financing Assurances Review, and Request for Waivers of Applicability: Staff Report and Press Release. (IMF Staff Country Reports; Country Report, 2012)
The Second Review Under the Stand-By Arrangement with St. Kitts and Nevis highlights that economic activity continued to contract in 2011 while the current account balance improved and banks remained sound. All quantitative performance criteria for end-December 2011 were met, and the structural benchmarks were completed. The authorities have made progress in a comprehensive debt restructuring, including a successful completion of the restructuring of bonds and external commercial debt on April 18, 2012, and agreement on a debt-land swap.